The effect of ego depletion or mental fatigue on subsequent physical endurance performance: A meta-analysis. Issue 1 (September 2019) - Giboin, Louis-Solal; Wolff, Wanja
Highlights: Ego depletion and mental fatigue impair subsequent endurance performance. The duration of the mental effort task doesn't predict the magnitude of impairment. The effect is higher on isolation than whole-body tasks. The effect is higher when the person-situation fit is low. This effect should not be seen only through the "fatigue" prism but also as "value". Abstract: Two independent lines of research propose that exertion of mental effort can impair subsequent performance due to ego depletion or mental fatigue. In this meta-analysis, we unite these research fields to facilitate a greater exchange between the two, to summarize the extant literature and to highlight open questions. We performed a meta-analysis to quantify the effect of ego-depletion and mental fatigue on subsequent physical endurance performance (42 independent effect sizes). We found that ego-depletion or mental fatigue leads to a reduction in subsequent physical endurance performance (ES = -0.506 [95% CI: -0.649, -0.369]) and that the duration of prior mental effort exertion did not predict the magnitude of subsequent performance impairment (r = -0.043). Further, analyses revealed that effects of prior mental exertion are more pronounced in subsequent tasks that use isolation tasks (e.g., handgrip; ES = -0.719 [-0.946, -0.493]) compared to whole-body endurance tasks (e.g. cycling; coefficient = 0.338 [0.057, 0.621]) and that the observed reduction in performance is higher when the person-situation fit is low (ES for high person-situation fit = -0.355 [-0.529, -0.181], coefficient for low person-situation fit = -0.336 [-0.599, -0.073]). Taken together, the aggregate of the published literature on ego depletion or mental fatigue indicates that prior mental exertion is detrimental to subsequent physical endurance performance. However, this analysis also highlights several open questions regarding the effects' mechanisms and moderators. Particularly, the surprising finding that the duration of prior mental exertion seems to be unrelated to subsequent performance impairment needs to be addressed systematically.